Heterotrimeric G-proteins facilitate resistance to plant pathogenic viruses in Arabidopsis thaliana (L.) Heynh. (2nd August 2016) - Brenya, Eric; Trusov, Yuri; Dietzgen, Ralf Georg; Botella, José Ramón
ABSTRACT: Heterotrimeric G-proteins, consisting of Gα, Gβ and Gγ subunits, are important signal transducers in eukaryotes. In plants, G-protein-mediated signaling contributes to defense against a range of fungal and bacterial pathogens. Here we studied response of G-protein-deficient mutants to ssRNA viruses representing 2 different families: Cucumber mosaic virus (CMV) ( Bromoviridae ) and Turnip mosaic virus (TuMV) ( Potyviridae ). We found that development of spreading necrosis on infected plants was suppressed in the Gβ-deficient mutant ( agb1-2 ) compared to wild type and Gα-deficient mutant ( gpa1-4 ). In accordance, ion leakage caused by viral infection was also significantly reduced in agb1-2 compared to wild type and gpa1-4 . Nevertheless, both viruses replicated better in agb1-2 plants, while gpa1-4 was similar to wild type. Analysis of pathogenesis-related genes showed that Gβ negatively regulated salicylic acid, jasmonic acid and abscisic acid marker genes during CMV and TuMV infections. Interestingly, analysis of salicylic acid deficient transgenic plants indicated that salicylic acid did not affect resistance against these viruses and did not influence the Gβ-mediated defense response. We conclude that heterotrimeric G-proteins play a positive role in defense against viral pathogens probably by promoting cell death.